Evaluation of The Design Conformity of Water Treatment Plant Units at PERUMDA Kota Palangka Raya Based on SNI 6774:2008 and Technical Literature: Evaluasi Kesesuaian Desain Unit Instalasi Pengolahan Air PERUMDA Kota Palangka Raya Berdasarkan SNI 6774:2008 dan Literatur - Rahmah, Rifky Annisa; Masduqi, Ali (Media Ilmiah Teknik Lingkungan (MITL), 2025)
Non-compliant design of water treatment units can reduce process efficiency and product water quality. This study aims to evaluate the design conformity of the existing Water Treatment Plant (WTP) units operated by PERUMDA Air Minum Kota Palangka Raya against SNI 6774:2008 and established technical literature. The evaluation focused on the intake, coagulation, flocculation, sedimentation, filtration, and reservoir units using a retro-commissioning approach. Data collection included field measurements and review of technical documents. The results revealed several non-conformities, such as a GT value of 4.8×10⁴ (standard >10⁵), sedimentation detention time of less than 2 hours, and an overflow rate of 13.99 m³/m²/hour (standard limit 11 m³/m²/hour). These findings highlight the need for gradual technical design adjustments to enhance treatment efficiency.